Biohacking Social: una estrategia pedagógica para el fortalecimiento de la educación y el fomento de la alfabetización científica en Medellín, Colombia - Cardona-Echeverry, Andrés; Posada-Ferez, Alejandra; Zapata-Martínez, Juan-Felipe (Revista Científica, 2023)
The impact of quality education and access to information on societies’ sustainable development is undeniable. A strategy focused on improving the quality of education and the democratization of science could be dubbed social biohacking. This work proposes a schools of creation model that integrates social actors with new technologies to solve problems such as the one considered in this work: deficiencies in the lab infrastructure of primary and secondary schools in countries like Colombia. Free software and do-it-yourself initiatives provide sustainable and replicable alternatives to address problems such as the lack of laboratory equipment, with the aim to guarantee a quality education environment. Additionally, this work relates the experience obtained by intervening communities in the city of Medellín through spaces for scientific dissemination and literacy as mechanisms for the democratization of science. Interventions in different communities demonstrate the importance of bringing science closer to everyday life, as well as its relevance to promote the social appropriation of knowledge.